Interprofessional Cooperation and Human Relationships in Prison: A Space for Resocialization (Praxis Educativa, 2026)
This article addresses the complex principle of re-education from a legal-normative and socio-pedagogical perspective, exploring how each organization that concretely embodies the institution can, through the educational and learning processes of inmates, translate this principle via the cooperation of knowledge. This gives rise to knowledge as a continuous process, shaped through mediation and sharing, where it is the institutional dialectic—encompassing the school, the professional figures operating within the prison, and the inmate’s willingness—that guides the process of resocialization. The article highlights the participatory importance of a symmetrical care relationship in educational terms, both among institutions and between the inmate and the community in which they are embedded. This relationship is essential in the delicate pathways that accompany inmates in the redefinition of their personal journey and must be based, within a shared prescriptive framework, on a transformation in the way of thinking and acting of those involved in these processes. The goal is to create and develop the concept of an inclusive educational community—one that is not merely the sum of educational actions, but rather one capable of overcoming the “oppressor-oppressed” dialectic. This model aims to integrate inmates positively and constructively into society through the practical application of the skills they have acquired, by uniting shared intentions.
Keywords: adult education; resocialization; cooperative skills; transformation